Effect of surfactant concentration on the responsiveness of a thermoresponsive copolymer/surfactant mixture with potential application on “Smart” foams formulations - Lencina, María Malvina Soledad (2018)
Hypothesis Previous efforts to formulate smart foams composed of mixtures of PNIPAAm, a thermoresponsive uncharged polymer, and surfactants have failed because the surfactant displaces the PNIPAAm from the liquid-air interface, removing the thermal responsiveness. We hypothesized that thermoresponsive foams could be formulated with such a mixture if a charged surfactant were used in order to anchor an oppositely charged brush-type polyelectrolyte, for which PNIPAAm could be incorporated as side chains, to the interface. Experiments A brush-type negatively charged co-polyelectrolyte (Cop-L) with PNIPAAm as side chains was synthetized. Its mixtures with DTAB, a cationic surfactant, in aqueous solution were characterized by dynamic light scattering, surface tension and surface compression viscoelasticity measurements, as a function of both surfactant concentration and temperature. The foam stability and its responsiveness to temperature changes were studied with a homemade apparatus. Findings The Cop-L/DTAB mixtures were capable of producing thermoresponsive foams but only in a very narrow surfactant concentration (cs) range, 0.3 < cs< 1.6 mM. The responsiveness is due to a modification of the interfacial compression elasticity induced by conformational changes of the Polyeletrolyte/surfactant aggregates at the interface. This is possible only for cs < 1.6 because higher surfactant concentrations induce the polymer collapse at all temperatures, eliminating the thermal responsiveness.